Analisis kebutuhan informasi pengguna pada Dinas Perpustakaan dan Kearsipan Kota Salatiga - Diana Syaputri; Siti Mahmudah (Nur Science Institute, 2026)
This study aims to analyze the information needs of users at the Regional Library (Perpusda) using a qualitative approach. Data were collected through in-depth interviews with librarians and surveys distributed to library users. The findings indicate that the library has provided collection request facilities through manual forms and digital barcodes; however, the realization of procurement is still constrained by time and budget limitations. Collection evaluation is conducted periodically through procurement meetings and weeding activities to maintain the relevance of the collection. On the other hand, user preferences are predominantly focused on fiction collections, while certain fields such as language and general works remain limited. The survey results reveal users’ needs for increased collection availability, more responsive service access, and improvements in the information retrieval system. These findings highlight the importance of two-way communication between librarians and users in formulating service policies that are more adaptive to evolving needs.